Physicochemical and bacteriological quality of swimming pools water in Kombolcha Town, Northeastern Ethiopia - Natnael, Tarikuwa; Hassen, Seada; Desye, Belay; Woretaw, Lebasie (Frontiers in Public Health, 2024)
Introduction: The use of swimming pool water for recreation, rehabilitation, and athletics is widespread around the world, especially in large Cities and Towns. However, poorly managed swimming pool water can facilitate the spread of illnesses connected to recreational water. Despite this, there is no evidence on quality of swimming pools water in Kombolcha Town. Therefore, this study was aimed to evaluate the physicochemical and bacteriological quality of swimming pools water in Kombolcha Town. Methods: A laboratory-based cross-sectional study was conducted from February to April, 2021 in Kombolcha Town. A total of 90 water samples were collected from the three outdoor swimming pools. The collected data of both physicochemical and bacteriological parameters were entered into Microsoft Excel 2010 and analysed using SPSS version 25.0. One-way ANOVA was used to test whether there were statistically significant differences between different swimming pools. The level of significance was declared at a p-value of <0.05. Results: In this study, out of all the pool water samples that were examined, 37.8% had pH values between 7.2 and 7.8, 36.7% had temperatures between 21°C and 32°C, and 26.7% had turbidity values that were within the WHO standard. Furthermore, only 16.7% of the pool water samples showed residual chlorine levels of 2-3 mg/l. In addition, only 27.8%, 35.6%, and 32.2% of the samples, respectively, met the WHO criterion for total coliform, faecal coliform, and heterotrophic plate count. Conclusion: The result indicates that most pool water samples did not fulfil both the physicochemical and bacteriological quality of the WHO standard limit for swimming pools. Thus, it is crucial to clean and regularly check the pool water, apply pool safety requirements, and raise pool user’s awareness about the danger of pool water pollution through training.